Impact of Different Annealing Processes on the Performance of Nylon-Based Artificial Muscles for the Use in Robotic Prosthetic Limbs - Atikah N.A.; Leong Y.W.; Anuar A. (Springer, 2023)
Annealing; Cooling; Durability; Fisheries; Polyamides; Prosthetics; Rayon; Robotics; Annealing process; Artificial muscle; Heating and cooling; Life span; Nylon fishing strings; Prosthetic limbs; Slow cooling; Slow heating; Muscle